Dominasi Struktur Birokrasi terhadap Inovasi Pelayanan Publik: Kajian Perspektif Teori Franpoort - Hatty Suat; Syaifulrijal Mahulauw; Judy de Fretes (JIMAD : Jurnal Ilmiah Multidisiplin, 2026)
This study examines how the dominance of bureaucratic structures influences innovation in public service delivery within governmental institutions. Using the analytical framework of Franpoort’s Theory, which conceptualizes bureaucracy as a system of formal structures, hierarchy, procedures, and control mechanisms, this research investigates whether these elements hinder or enable innovation in public organizations. Employing a qualitative case study approach in selected Indonesian public service units, data were collected through in-depth interviews, observations, and document analysis. The findings reveal that highly rigid bureaucratic structures tend to suppress flexibility, discourage individual initiatives, and slow down the adoption of new ideas. However, when bureaucratic dominance is balanced with supportive organizational culture and innovative leadership, bureaucracy can serve as a framework that stabilizes and sustains innovation. This study contributes to public administration theory by reinterpreting bureaucratic dominance through Franpoort’s perspective, emphasizing that bureaucracy and innovation are not necessarily contradictory but can be complementary under adaptive institutional arrangements. The results highlight the need for structural reform and leadership strategies that foster creativity, cross-functional collaboration, and responsive governance in public service delivery.